Blood pressure and heart rate in pregnant and non-pregnant bitches - Cahua U., Jacqueline (2023)
The aim of this study was to determine the effect of pregnancy on blood pressure and heart rate in female dogs aged 11 months to 9 years, apparently healthy. Blood pressure and heart rate were measured in 156 female dogs of various breeds, 124 of which were pregnant. The females were taken to consultation to determine possible pregnancies. Body weight, body condition score, presence of subcutaneous oedema and age of the patient were recorded. Gestation length, number of foetuses and presence of hydrops fetalis were calculated by ultrasound. Blood pressure and heart rate (HR) were measured with a SunTech Vet30® monitor. The results showed a significant increase (p=0.013) in HR in pregnant dogs (pregnant: 136 beats/min, non-pregnant: 129 beats/min); however, no variation was found due to the effect of weight, age, number of foetuses, presence/absence of hydrops fetalis and subcutaneous mammary oedema between both groups. Systolic blood pressure (SBP) did not vary in pregnant dogs, but diastolic blood pressure (DBP) (p=0.006) and mean arterial pressure (MAP) (p=0.011) were significantly lower compared to non-pregnant dogs. The number of foetuses did not significantly influence SBP, but DBP (p=0.02) and MAP (p=0.035) were significantly lower in dogs with higher number of foetuses.